2017
DOI: 10.1002/mgg3.320
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sequence data to identify potential risk variants for oral clefts in multiplex families

Abstract: BackgroundNonsyndromic oral clefts are craniofacial malformations, which include cleft lip with or without cleft palate. The etiology for oral clefts is complex with both genetic and environmental factors contributing to risk. Previous genome‐wide association (GWAS) studies have identified multiple loci with small effects; however, many causal variants remain elusive.MethodsIn this study, we address this by specifically looking for rare, potentially damaging variants in family‐based data. We analyzed both whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
1
13
0
3
Order By: Relevance
“…In this study, the variable low schooling presented itself as a protective factor in the quadrennium 2005-2008, but it is known that the lack of information is an aggravating factor in health, being the low schooling a predominant Brazilian feature in the profile of neonatal deaths. 5,6,21 It is emphasized that, from 2009 to 2016, the low schooling was demonstrated as a risk to the fissure, corroborating the literature. 22 In Argentina it was found that the maternal and paternal schooling are also considered risk factors for fissures, 18 as well as in Vietnam, where the low schooling is associated with higher chances of fissure.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In this study, the variable low schooling presented itself as a protective factor in the quadrennium 2005-2008, but it is known that the lack of information is an aggravating factor in health, being the low schooling a predominant Brazilian feature in the profile of neonatal deaths. 5,6,21 It is emphasized that, from 2009 to 2016, the low schooling was demonstrated as a risk to the fissure, corroborating the literature. 22 In Argentina it was found that the maternal and paternal schooling are also considered risk factors for fissures, 18 as well as in Vietnam, where the low schooling is associated with higher chances of fissure.…”
Section: Discussionsupporting
confidence: 78%
“…5 Cleft lip and/or cleft palate are due to problems in the process of development during the embryonic or fetal period, causing the disability or lack of fusion between the tissues that comprise these structures. 6 The etiology of the anomaly of lip and/or palate is still not well defined; however, studies show that between 25 and 30% of the cases are the result of hereditary factors, and 70 to 80% have a multifactorial etiology, involving among other things, maternal habits of life during pregnancy (diet, alcohol, tobacco and drugs). 1,7 Various problems arising from the presence of cleft lip and/or cleft palate may affect its patient since birth, such as difficulties in breastfeeding due to impaired sucking, swallowing and breathing; disorders in hearing and phonation, with losses in communication, in addition to the low social acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…As a genetically complex disease, NSCL/P may have multiple genetic models, including dominant (Birnbaum et al, 2008;Holzinger et al, 2017;Tian et al, 2017) and recessive inheritance (Marazita et al, 2004;Moura, Cirio, & Pimpao, 2012). Based on the family pedigree information in this study, an autosomal dominant Mendelian inheritance model was considered the best fit, although we cannot eliminate the possibility of de novo, homozygous, or compound heterozygous models.…”
Section: Discussionmentioning
confidence: 99%
“…In one Syrian pedigree, the 8 affected relatives did not have any known common ancestor, so a sub-pedigree including 6 affected relatives descending from a common couple of ancestors was used in the analysis, reducing the total number of affected subjects to 151 (Table 2). The sequencing, alignment, and variant calling process was described in Holzinger et al [2017], who also reported on RVs observed in the WGS data from the Filipino and Syrian families.…”
Section: Methodsmentioning
confidence: 99%